EMBRACING VULNERABILITY AS KENOSIS IN HENRI NOUWEN’S SPIRITUAL JOURNEY AND ITS RESONANCE WITH IGNATIAN SPIRITUALITY - Marhenanto, Septian (Spiritualitas Ignasian: Jurnal Kerohanian dalam Dunia Pendidikan, 2025)
This article examines how Henri Nouwen’s theology of vulnerability, grounded in his personal struggles and pastoral experiences, reinterprets Christ’s kenosis (self-emptying) as a transformative spiritual practice. The study aims to analyze the resonance between Nouwen’s spiritual journey and the principles of Ignatian spirituality, particularly the Spiritual Exercises of St. Ignatius Loyola. Employing a qualitative literature research method, the article draws on Nouwen’s autobiographical writings and key Ignatian texts, using comparative and hermeneutic analysis to highlight both similarities and distinctions. The results show that while Nouwen was not directly shaped by Ignatian spirituality, his approach to discernment, daily reflection, and accompaniment in weakness naturally aligns with Ignatian themes. The article concludes that embracing vulnerability as kenosis not only deepens personal spiritual growth but also offers a resilient model for pastoral ministry in contemporary contexts. This synthesis deepens our understanding of Christian formation, highlighting that human fragility can be a sacred space for encountering God and fostering authentic community.